Identification and Analysis of the Industrial Districts in Spain: A Quantitative Approach - Jose Miguel Giner Perez; Antonio Fuster Olivares; Maria Jesus Santa Maria Beneyto (European Regional Science Association (ERSA), 2006)
The identification and analysis of the industrial districts in Spain using a quantitative approach is the aim of this research. In the first part, the industrial districts are identified applying the methodology developed by the Italian Statistics Institute (ISTAT). This identification is possible due to the availability of information about the local labour markets; these have been estimated with labour mobility data between municipalities and the industrial data used to analyse the location of the Spanish industry comes from the Industrial Register published by the Ministry of Industry, Tourism and Commerce. This statistical source classifies the different industrial activities in 23 sectors. In the second part, the characteristics of the, previously identified, industrial districts are quantitatively analysed and the results are compared with those obtained in other similar researches developed in Spain and Italy. Some of the characteristics that will be analysed are the relevance of the industrial districts for the Spanish industry (in a national, sectorial and regional level), the industrialization degree, the sectorial specialization level or the predominance of small and medium enterprises in the whole industry or by sectors. Finally, with the quantitative results, a typology of the industrial districts in Spain will be constructed, that could be used in a further analysis based in qualitative techniques.
Keywords: 330